Infectious Agents As Markers of Human Migration toward the Amazon Region of Brazil - Ishak, Ricardo; Machado, Luiz F. A.; Cayres-Vallinoto, Izaura; Guimarães Ishak, Marluísa de O.; Vallinoto, Antonio C. R. (Frontiers in Microbiology, 2017)
Infectious agents are common companions of humans and since ancient times they follow human migration on their search for a better place to live. The study of paleomicrobiology was significantly improved in its accuracy of measurement with the constant development of better methods to detect and analyze nucleic acids. Human tissues are constantly used to trace ancient infections and the association of anthropological evidences are important to confirm the microbiological information. Infectious agents which establish human persistent infections are particularly useful to trace human migrations. In the present article, the evidence of infection by viral agents such as human T-lymphotropic virus 1, human T-lymphotropic virus 2, human herpes virus-8, JC virus, and a bacterium, Chlamydia trachomatis, was described using different methodologies for their detection. Their presence was further used as biomarkers associated with anthropological and other relevant information to trace human migration into the Amazon region of Brazil. The approach also evidenced their microbiological origin, emergence, evolution, and spreading. The information obtained confirms much of the archeological information available tracing ancient and more recent human migration into this particular geographical region. In this article, the paleomicrobiological information on the subject was summarized and reviewed.